Islam dan Civil Society - Imam Sukardi (TSAQAFAH, 2010)
The article tries to address the concept of civil society from varied perspectives. From a historical point of view, civil society demands not only the absent domination of state but also liberates individuals from the hegemony of state. The article shows that in Indonesia and Malaysian discourse, masyarakat madani is often used to represent the term of civil society. Using this conception, major values of civil society also share with basic ideas within the Medina Treaty in the history of Islam. These ideas include egalitarianism, human rights protection, participation, law and justice enforcement and pluralism. In this frame, the question on whether or not Islam is compatible with the concept of civil society is clearly answered. Muslims could benefit such a concept to build their awareness of being progressive and adaptive to social changes.